Fecal Calprotectin Level as Diagnostic Marker for Intestinal Inflammation in Inflammatory Bowel Disease Patients - Darmadi -; Dadang Makmun; Andri Sanityoso; Hamzah Shatri (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Inflammatory bowel disease diagnosis was still based on invasive examination, such as endoscopy and histopathology. Fecal calprotectin was a non-invasive intestinal inflammation marker, but several study give a different result in its diagnostic value and correlation to inflammatory bowel disease. This research was aimed to prove that fecal calprotectin examination has a high diagnostic value in diagnosing inflammatory bowel disease, and also correlate to its clinical stages.Method: This is a cross sectional study to do a diagnostic test in several hospital in Jakarta, from September 2014 to February 2015. Receiver operating characteristic (ROC) curve was made to get fecal calprotectin diagnostic level and Krusskal Wallis test was performed to identify fecal calprotectin difference among each inflammatory bowel disease clinical stages.Results: A total of 71 patients with inflammatory bowel disease was invoved in this research, based on colonoscopic examination result. Among them, 57 patients was confirmed to have intestinal inflammation based on histopathology result. Fecal calprotectin level was found to be higher in patients with inflammatory bowel disease than patients without intestinal inflammation (553,8 µg/g vs. 76,95 µg/g, p 0,001). A cut off point of 179,3 µg/g was gathered, with 96% sensitivity (95% CI: 0,88-0,99), 93% specificity (95% CI: 0,69-0,99), and 99,5% area under curve (AUC) 99,5% (95% CI: 0,98-1,00). A significant difference was found between fecal calprotectin in each inflammatory bowel disease clinical stages (p 0,001).Conclusion: Fecal calprotectin has a high diagnostic value for inflammatory bowel disease (IBD) and strongly correlate to its disease clinical stages.